A postcolonial reading of selected arabic novels translated into English - Yahya Alwadhaf, Yahya Hassan (2008)
The novel genre is not an indigenous Arabic literary form in the contemporary Arabic literature, but an imported and borrowed one that arrived with the European ambitions of domination and expansion. It is a purely twentieth century phenomenon that passed through different stages of its formation. Beginning with translation of Western novels, imitation, and ultimately indigenization, the Arabic novel is a recognized universal genre. One aspect of this recognition is the translation of a considerable number of novels into English and other languages. Up to the year 2001, more than one hundred novels had been translated into English. Unfortunately, this type of novel has no status, still in search for a status both in the Arabic culture and in world literature. The majority of these novels remained unknown and undiscovered in the critical literary circles both in the Arab world and in the Western literary tradition. Many studies have been conducted on the Arabic novel in translation, nevertheless, in many cases the focus is centered on the Egyptian novel in general and on the Mahfouzean on particular. This study attempts to locate the contemporary Arabic novel in the main stream of world literature and in particular as part of the genre of postcolonial literature. To achieve this end, the focus is directed on a body of literary texts that had been translated from Arabic into English and have been neglected so far in the postcolonial studies. Four texts have been selected from peripheral places in the Arabic world to be studied and analyzed concentrating on themes and techniques. Reading through the postcolonial theory as well as the narrative theory, it is argued that Mohamed Abdul Wali, Ghassan Kanafani, Tayeb Salih and Jabra Ibrahim have subscribed significantly to the postcolonial studies by discussing issues such as identity formation, body-land association, resistance, hybridity, mimicry and the conflict between tradition and modernity. Furthermore, they have manipulated a variety of narrative techniques and discursive strategies such as parody, irony, intertextuallity to highlight and enrich thematic treatment. This study makes use of the ideas of Edward Said, Homi Bhabha, Norman Friedman, Mark Schorer among others to examine the postcolonial and technical dimensions of They Die Strangers, Men in the Sun, Season of Migration to the North and The Ship